Prevalence and Clinical Significance of Latent Brugada Syndrome in Atrial Fibrillation Patients Below 45 Years of Age - Ghaleb, Ramadan; Anselmino, Matteo; Gaido, Luca; Quaranta, Stefano; Giustetto, Carla; Salama, Mohammed Kamal; Salh, Ayman; Scaglione, Marco; Fathy, Enas; Gaita, Fiorenzo (Frontiers in Cardiovascular Medicine, 2020)
Aim To describe prevalence and clinical significance of latent Brugada syndrome (BrS) in a young population with atrial fibrillation (AF). Methods Between September 2015 and November 2017, among 111 AF patients below 45 years of age, those without pre-existing pathologies and/or known risk factors were selected for the study. Based on baseline 12 lead-24H Holter electrocardiogram (ECG), previous class 1C antiarrhythmic drug therapy or ajmaline testing, patients were stratified as latent type 1 BrS or not. Results Within the 78 enrolled patients, 13 (16.7%; group 1) revealed a type 1 BrS ECG pattern, while 65 (83.3% group 2) did not. Mean age was 37±8 vs 35±7 (p = 0.42), and males were 7 (54%) vs 54 (83%) (p = 0.02) in the two groups, respectively. Family history of BrS was significantly more common within group 1 patients (2, 15% vs 0; p = 0.03), and 4 (31%) patients experienced syncope in group 1 vs 5 (8%) in group 2 (p = 0.02). After a mean follow up of 42±18 months from the index AF event more than 80% of the patients, in both study groups, was in sinus rhythm. Conclusion In young patients with AF without pre-existing pathologies and/or known risk factors, latent BrS should be suspected. Syncope and a family history of BrS emerge as easily identifiable factors related to BrS. Long-term sinus rhythm maintenance appears satisfactory, either in the presence or not of BrS.